Taxonomy and paleobiogeography of rudist bivalves from Upper Cretaceous strata, Gulf Coastal Plain and Puerto Rico, USA. (March 2023) - Zimmerman, Alexander N.; Johnson, Claudia C.; Phillips, George E.; Ehret, Dana J.
Abstract: This study provides the first focused investigation of rudist bivalves from the Upper Cretaceous of the Gulf Coastal Plain (GCP) in the southern US and previously undescribed specimens from the Flor de Alba Limestone Member of the Pozas Formation in Puerto Rico. Identified rudists from the GCP comprise the Monopleuridae, including Gyropleura, as well as Radiolitidae, including Biradiolites cardenasensi, Durania maxima, Guanacastea jamaicensis, Radiolites acutocostata, and Sauvagesia . Integrating rudist occurrences within well-established GCP biostratigraphy allows for extension of upper ranges of D . maxima and R . acutocostata into the late Campanian, and extension of the lower ranges of B . cardenasensis and G . jamaicensis into the early Campanian. Identified rudists from Puerto Rico comprise the Hippuritidae and include Barrettia monilifera, which supports the age of the Flor de Alba Limestone Member of the Pozas Formation as middle Campanian. Combined taxonomic, biostratigraphic, and paleobiogeographic analyses indicate there is no rudist fauna endemic to the GCP, and the region marks the northeastern range of the Caribbean genera Biradiolites, Durania, Guanacastea, Gyropleura, Radiolites, and Sauvagesia during the Campanian and Maastrichtian. The new occurrences help inform future updates of Late Cretaceous sea surface-current reconstructions for the Caribbean and Western Interior Seaway, USA.